2022
DOI: 10.21037/atm-22-812
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of magnetic resonance imaging and computed tomography in the diagnosis of acute pancreatitis: a systematic review and meta-analysis of diagnostic test accuracy studies

Abstract: Background: Acute pancreatitis (AP) is characterized by acute onset, rapid development, and poor prognosis. Timely diagnosis and identification of the cause are the key to formulating the clinical program and improving the prognosis. There were several studies on this topic but the results varied. This study systematically evaluated and analyzed reports on the comparison of magnetic resonance imaging (MRI) and computed tomography (CT) for the diagnosis of AP in recent years, providing evidence for clinical dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The findings are consistent with the study by Irshad et al, 22 and Banday et al, also suggested mCTSI to be a simple and accurate scoring tool as compared to Balthazr CT severity index and mCTSI to have a significant correlation with clinical outcomes in terms of duration of hospitalization, development of complications, and overall mortality. 6 However a systematic and meta-analysis of diagnostic accuracy studies have concluded magnetic resonance imaging (MRI) to be more specific, sensitive and accurate as compared to CT. 23 MRI has higher recognition ability for diagnosis of pancreatic injury in terms of peripancreatic effusion, pancreatic contour, and vascular proliferation at site of lesion. 24,25 Despite advances in diagnosis and management, CRP and mCTSI scores have their predictive value in risk stratification and aid in management.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are consistent with the study by Irshad et al, 22 and Banday et al, also suggested mCTSI to be a simple and accurate scoring tool as compared to Balthazr CT severity index and mCTSI to have a significant correlation with clinical outcomes in terms of duration of hospitalization, development of complications, and overall mortality. 6 However a systematic and meta-analysis of diagnostic accuracy studies have concluded magnetic resonance imaging (MRI) to be more specific, sensitive and accurate as compared to CT. 23 MRI has higher recognition ability for diagnosis of pancreatic injury in terms of peripancreatic effusion, pancreatic contour, and vascular proliferation at site of lesion. 24,25 Despite advances in diagnosis and management, CRP and mCTSI scores have their predictive value in risk stratification and aid in management.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has also confirmed this point demonstrating the EPIM score to be more helpful in evaluating the severity of AP than either the MRSI and MMRSI in the early stage of AP ( 7 , 20 ). Another possible reason may be that MRI is more sensitive than CT in detecting slight changes of mild inflammation and effusion ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis encompassing a total of 566 patients, MRI demonstrated superior accuracy and sensitivity compared to CT for diagnosing AP[ 89 ]. While no study has yet shown that MRI can decrease AP mortality or enhance prognosis, MRI serves as an invaluable diagnostic tool for distinguishing individuals with suspected AP and is regarded as the premier imaging choice for the clinical diagnosis of AP[ 89 ].…”
Section: Imaging Technologymentioning
confidence: 99%
“…In a meta-analysis encompassing a total of 566 patients, MRI demonstrated superior accuracy and sensitivity compared to CT for diagnosing AP[ 89 ]. While no study has yet shown that MRI can decrease AP mortality or enhance prognosis, MRI serves as an invaluable diagnostic tool for distinguishing individuals with suspected AP and is regarded as the premier imaging choice for the clinical diagnosis of AP[ 89 ]. Tang et al [ 82 ], utilizing MRI and APACHE II, devised a novel model through logistic regression for the early prediction of AP severity and ascertained that the combined model of extrapancreatic inflammation on MRI (EPIM) and APACHE II excelled in predicting AP severity, surpassing individual parameters.…”
Section: Imaging Technologymentioning
confidence: 99%